Pengaruh Pengetahuan dan Metode Pendaftaran Pasien Terhadap Waktu Tunggu di RSUD Kepohbaru - Silvia Putri Rahmawati; Nihayatul Munaa; Faizatul Ummah (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2026)
Outpatient waiting time is a key indicator of hospital service quality and significantly influences patient satisfaction. Although the maximum standard for outpatient waiting time is 60 minutes, data from Kepohbaru Regional General Hospital show an average waiting time of 113.4 minutes. This study aimed to examine the relationship between patients’ knowledge of service flow procedures, registration methods (offline and online), and outpatient waiting time. A quantitative cross-sectional design was employed, involving 89 outpatients selected through consecutive sampling. Data were analyzed using one-way ANOVA and independent t-tests. The findings revealed a significant association between patients’ knowledge of service flow procedures and outpatient waiting time (p<0.05). Registration method was also significantly associated with waiting time (p<0.05), with patients using online registration experiencing shorter waiting times than those using offline registration. These results suggest that improving patients’ understanding of service procedures and optimizing online registration systems may enhance service efficiency and reduce waiting times. Therefore, hospitals should strengthen patient education initiatives and further develop digital registration services to improve the quality and timeliness of outpatient care.